2014
DOI: 10.1136/annrheumdis-2013-204653
|View full text |Cite
|
Sign up to set email alerts
|

Abatacept treatment reduces disease activity in early primary Sjögren's syndrome (open-label proof of concept ASAP study)

Abstract: 2009-015558-40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(122 citation statements)
references
References 18 publications
(9 reference statements)
7
108
0
3
Order By: Relevance
“…The improvement verified in the ESSPRI of patients in the present study after periodontal therapy was similar to that found by studies evaluating the effects of using rituximab and abatacept for 4 weeks on disease symptoms. 37,38 In the present study, we also found a low correlation between the ESSPRI and the ESSDAI indexes (r = 0.31); this reinforces the need to associate the assessments of these important indexes in relation to pSS, as pointed out by Seror et al 39 Moreover, there were no significant changes in the medications and the dosage along the experimental periods of the present study. Therefore, it can be suggested that the periodontal treatment itself may be the only factor responsible for the improved salivary flow and quality of life of patients with pSS.…”
Section: Discussionsupporting
confidence: 54%
“…The improvement verified in the ESSPRI of patients in the present study after periodontal therapy was similar to that found by studies evaluating the effects of using rituximab and abatacept for 4 weeks on disease symptoms. 37,38 In the present study, we also found a low correlation between the ESSPRI and the ESSDAI indexes (r = 0.31); this reinforces the need to associate the assessments of these important indexes in relation to pSS, as pointed out by Seror et al 39 Moreover, there were no significant changes in the medications and the dosage along the experimental periods of the present study. Therefore, it can be suggested that the periodontal treatment itself may be the only factor responsible for the improved salivary flow and quality of life of patients with pSS.…”
Section: Discussionsupporting
confidence: 54%
“…In an open-label pilot study of abatacept in active pSS, patients with recent onset of pSS and high disease activity were monitored. During the intravenous abatacept treatment, ESSDAI, ESSPRI, rheumatoid factor, and IgG levels decreased significantly, and fatigue and health-related quality of life improved significantly [16]. Abatacept also induces clinical improvement in patients with severe and treatment-resistant diffuse SSc [15].…”
Section: Cd80/cd86 Cd28 and Ctla-4mentioning
confidence: 87%
“…Being chronic systemic autoimmune diseases, permanent activation of the adaptive immune system is obvious in both pSS and SSc [12,13]. The recognition of the outstanding importance of the costimulatory regulation in many autoimmune diseases and in tumor-immunology has lead to highly effective targeted therapies in both fields [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[115] Two small open-label trials of IV abatacept treatment in pSS have shown that abatacept decreases ESSDAI, ESSPRI, IgG, and rheumatoid factor, improves fatigue and decreases glandular inflammation. In the study by Meiners et al, [116] mild-tomoderate infusion reactions occurred in 40% of the patients in <1 hour of infusion (mostly hypotension and dizziness), and infections occurred in 66% of patients (mostly mild upper respiratory tract infections). Adler et al did not include a safety analysis plan in their methods, but did report that 27% of the patients experienced an AE, of which one was infectious (diverticulitis).…”
Section: Abataceptmentioning
confidence: 99%